Potential Pharmacokinetic Drug-Drug Interactions between Cannabinoids and Drugs Used for Chronic Pain - Vázquez, Marta Mabel (2020)
Choosing an appropriate treatment for chronic pain remains problematic, and despite the available medication for its treatment, still, many patients complain about pain and appeal to the use of cannabis derivatives for pain control. However, few data have been provided to clinicians about the pharmacokinetic drug-drug interactions of cannabinoids with other concomitant administered medications. Therefore, the aim of this brief review is to assess the interactions between cannabinoids and pain medication through drug transporters (ATP-binding cassette superfamily members) and/or metabolizing enzymes (cytochromes P450 and glucuronyl transferases).